(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Sands are typically compacted in the field using a variety of machinery, with the compaction energy varying greatly. The relative density is a better indicator for determining granular soil compaction. It can be more beneficial in the field if the relative density can be associated simply by any index property of the granular soil. The voids ratio is used to define relative density. The minimum and maximum voids ratios are known to be dependent on the mean grain size. However, when different energy levels are considered, there is no clear relationship for the void’s ratio in terms of grain size. As a result, the effect of mean grain size on the relative density of sand has been investigated in this dissertation under various compaction energies.The voids ratio for standard, modified, reduced standard, and reduced modified energy levels. The simple nonlinear empirical relations have been derived by correlating Proctor tests with mean grain size. The proposed method estimates the relative density with a percentage variance of less than 5% of the measured value. The relative density correlations mentioned above will be useful for field design standards. Nano silica particles and artificial pozzolans, according to the study, can improve the structural qualities of cement based materials. The influence of cement and Nano silica on the engineering parameters (compaction, unconfined compressive strength) of sand has been studied in the literature. According to the study’s findings, the inclusion of nano silica. The results of the study presented that the addition of the nano silica improves the engineering properties of sands.